Efektivitas Penggunaan Platelet-Rich Plasma (PRP) dalam Proses Penyembuhan Tulang pada Model Hewan Coba: Systematic Review - Noverial Noverial; Biomechy Oktomalio Putri (Fakultas Kedokteran, Universitas Andalas, 2022)
Bone injury causes thus, reduced productivity and death in the sufferer. Alternative treatment research was developed to speed up the bone healing process, including autologous treatments such as Platelet-Rich Plasma (PRP). Objective: To assessed the effectiveness of PRP use in the bone healing process on studies with experimental animal models. Methods: This study was a systematic review research whose article searches through the databases such as PubMed, ScienceDirect and ProQuest on English-language articles published from 2012-2022. The keywords used were ((bone healing OR fracture healing OR bone defect) AND (platelet rich plasma OR prp) AND (animal models)). Results: PRP was effective in accelerating bone regeneration in every experimental animal model in the early phases of healing, but not all studies have significant differences between groups that used PRP and those who did not. Conclusion: PRP has a positive impact in increasing bone mineral density, but the effectiveness of using PRP may vary from study result to study result, depending on the characteristics of the experimental animal model used in the study and the accuracy of concentration in the administration of PRP.Keywords: animal models, bone healing, platelet-rich plasma